WNL we never looked: vulvar carcinoma incidence after screening cutoff - Amaris N. Geisler, MD; Jodi E. Ganz, MD (Wolters Kluwer, 2024)
The incidence of vulvar carcinoma increases with age, though elderly women receive less aggressive cancer therapies and fewer strategies aimed at cancer prevention. Furthermore, elderly women dual enrolled in Medicaid-Medicare experience poor survival rates for vulvar carcinoma. Herein, we provide recommendations for the prevention of and guidelines for the multidisciplinary care of vulvar carcinoma. Prevention of vulvar carcinoma can be categorized into primary, secondary, and tertiary prevention. Primary prevention consists of vaccination, secondary prevention consists of screening, and tertiary prevention is aimed at the management of premalignant and early-stage lesions.